2003
DOI: 10.1086/377139
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a Susceptibility Gene for Type 2 Diabetes to Chromosome 5q34–q35.2

Abstract: We report a genomewide linkage study of type 2 diabetes (T2D [MIM 125853]) in the Icelandic population. A list of type 2 diabetics was cross-matched with a computerized genealogical database clustering 763 type 2 diabetics into 227 families. The diabetic patients and their relatives were genotyped with 906 microsatellite markers. A nonparametric multipoint linkage analysis yielded linkage to 5q34-q35.2 (LOD = 2.90, P=1.29 x 10(-4)) in all diabetics. Since obesity, here defined as body mass index (BMI) > or =30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 65 publications
0
96
0
6
Order By: Relevance
“…They were ϳ1-25 cM wide, with linkage evidence at significance levels up to P Ͻ 0.001. These results illustrate the advantage of refined scans, such as ours or the ones routinely used now by teams such as the investigators at Decode Genetics (13)(14)(15), to detect most putative disease regions.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…They were ϳ1-25 cM wide, with linkage evidence at significance levels up to P Ͻ 0.001. These results illustrate the advantage of refined scans, such as ours or the ones routinely used now by teams such as the investigators at Decode Genetics (13)(14)(15), to detect most putative disease regions.…”
Section: Discussionmentioning
confidence: 53%
“…Use of a denser marker map may increase power and better smooth the logarithm of odds (LOD) score curve, enabling more accurate assessment of the linkage evidence. The personnel at Decode Genetics (Reykjavik, Iceland) routinely perform genome scans with 1,000 markers, i.e., a mean marker spacing of 4 cM (13)(14)(15). Computer simulations allow more accurate assessment of the significance of the results.…”
mentioning
confidence: 99%
“…In the past few years it became feasible to genotype cheaply large pedigrees with much greater numbers of microsatellites than were previously used for genome scans, and statistical programs that are now available permit efficient computation of linkage even in complex pedigrees 28,29 . These advances allowed a substantial increase in the scale of pedigree-based linkage studies 2,4,[30][31][32][33][34][35][36][37][38] . Inadequate technology and statistical methodology have similarly hindered implementation of alternatives to pedigreebased mapping.…”
Section: Appropriate Technology and Statistics For Each Approachmentioning
confidence: 99%
“…Recently, Reynisdottir et al [2] found suggestive linkage of type 2 diabetes to chromosome 10q in the Icelandic population. Fine-mapping with 228 microsatellite markers in Icelandic individuals with type 2 diabetes and controls throughout a 10.5 Mb interval on 10q identified one microsatellite marker, DG10S478 in intron 3 of the TCF7L2 gene, as being strongly associated with type 2 diabetes (p ¼ 2:1 Â 10 À9 ) [3].…”
Section: Introductionmentioning
confidence: 98%